Complicaciones a largo plazo de la parálisis cerebral espástica - López-Huamanrayme, Eddy; Tárraga-Granilla, Liz V.; Rozas-Latorre, Marisabel (Revista del Cuerpo Médico Hospital Nacional Almanzor Aguinaga Asenjo, 2019)
Galería Fotográfica (sin resumen)